Active Phasor Data Concentrator performing adaptive management of latency. (December 2018) - Castello, Paolo; Muscas, Carlo; Pegoraro, Paolo Attilio; Sulis, Sara
Abstract: The Phasor Data Concentrator (PDC) is a function in charge to receive and combine the time-tagged synchrophasor data from Phasor Measurement Units (PMUs). The tasks of the PDC can include data handling, processing, and storage. Collected data are forwarded to the next higher-level element of the hierarchical monitoring architecture, which means either an operational center or a higher level PDC. Definitions of the terminology, functional descriptions and the test procedures concerning the PDC can be found in the guide IEEE C37.244-2013. In particular, in order for the PDC to ensure good latency performance, its interfacing with both the lower hierarchical level (i.e. PMUs with different features) and the higher one must be done in a reasonable time. It is worth noting that, while PMUs and PDCs were originally conceived for transmission systems, they are now expected to become key elements also for the monitoring of modern distribution grids. In this evolving and complex scenario, the PDC could play a crucial and active role. In this paper, an active PDC with advanced functionalities is proposed to manage the delay of several PMU streams so that an original adaptive data aggregation policy is implemented to allow compliance with time constraints of real-time applications.